Reseña/Review (Vaidhyanathan, Siva, “Anti-social media. How Fa-cebook disconnects us and undermines democracy” New York, Ox-ford University Press, ISBN: 978-019-0841-16-4, 276 págs., 2018) - Castellet Homet, Andreu (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2021)
Reseña/Review (Vaidhyanathan, Siva, “Anti-social media. How Facebook disconnects us and undermines democracy” New York, Oxford University Press, ISBN: 978-019-0841-16-4, 276 págs., 2018)